Yield performance and heat unit requirement of wheat (Triticum aestivum) varieties as affected .by sowing dates under rainfed conditions - SANDHU, I S; SHARMA, A R; SUR, H S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted at Ballowal Saunkhri, Punjab for 5 consecutive years (1992-93 to 1996-97) to study theeffect of varying sowing dates (25 October,4 November, 14 November and 24 November) on yield perfonnance andheat-unit requirement of different wheat (Triticum aeslivum L. emend. Fiori & Paol.) varieties('PBW 175','PBW 299', 'PBW 320' and 'PBW 359') under rainfed conditions. The crops sown on 25 October produced consistentlybetter grain yields, which decreased with delay in sowing. 'PBW 175' wheat gave the highest yield followed by'PBW 299'. The total crop growth duration as well as the heat units decreased with delay in sowing but the occurrenceof different growth stages showed a variable response to dates of sowing. The number of days taken for seedlingemergence and jointing increased with a concomitant decrease in the duration of reproductive phase, particularly flowering to maturity.Heat units did not vary much during seedling emergence but increased during emergence tojointing and decreased during jointing to flowering, particularly ip case of sowing after 4 November. There was aconspicuous decrease in heat units during flowering to maturity with delay in sowing due to shortening of the ripening period.The coefficient of variation for the total heat units at different sowing dates was low (3-4%), suggesting thatoccurrence of various growth stages of wheat can be reasonably well predicted under the rainfeq conditions of Kandi area.